2007
DOI: 10.3892/or.18.1.273
|View full text |Cite
|
Sign up to set email alerts
|

GP7 induces internucleosomal DNA fragmentation independent of caspase activation and DNA fragmentation factor in NB4 cells

Abstract: DNA fragmentation into internucleosomal fragments is the best recognized biochemical event of apoptosis. Two major caspase pathways have been identified in the signal transduction leading to DNA fragmentation: the receptor pathway and the mitochondrial pathway. DNA fragmentation factor (DFF) has been identified as a major apoptotic endonuclease in the internucleosomal DNA fragmentation process. However, the potential roles of caspases and DFF in internucleosomal DNA fragmentation induced by specific stimuli st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Indeed, it is known that selenite induces topoisomerase II–DNA complexes in cells, with a potential link to the induction of apoptosis Nitroxide-free radical to generate spin-labeled probes. Different series of spin-labeled etoposides have been described, including compounds with immunosuppressive properties and, recently, molecules such as the antioxidant cytotoxic derivative 15 (Figure ) and GP-7 characterized as a proapoptotic agent capable of down-regulating PgP Aroylthiourea derivatives, able to interfere with both tyrosine kinases and topoisomerases.…”
Section: Epipodophyllotoxins Forevermentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it is known that selenite induces topoisomerase II–DNA complexes in cells, with a potential link to the induction of apoptosis Nitroxide-free radical to generate spin-labeled probes. Different series of spin-labeled etoposides have been described, including compounds with immunosuppressive properties and, recently, molecules such as the antioxidant cytotoxic derivative 15 (Figure ) and GP-7 characterized as a proapoptotic agent capable of down-regulating PgP Aroylthiourea derivatives, able to interfere with both tyrosine kinases and topoisomerases.…”
Section: Epipodophyllotoxins Forevermentioning
confidence: 99%
“…Nitroxide-free radical to generate spin-labeled probes. Different series of spin-labeled etoposides have been described, including compounds with immunosuppressive properties and, recently, molecules such as the antioxidant cytotoxic derivative 15 (Figure ) and GP-7 characterized as a proapoptotic agent capable of down-regulating PgP…”
Section: Epipodophyllotoxins Forevermentioning
confidence: 99%
“…Qi et al. reported that GP‐7, a new spin‐labeled derivative of PPT, activated the caspase signaling pathway by releasing cytochrome c . In tumor necrosis factor α (TNF‐α) induced human aortic smooth muscle cells, deoxy‐PPT strongly inhibited matrix metalloproteinases (MMP‐9) expression and migration, as well as mRNA transcription of MMP‐9 gene expression and phosphorylation of ERK 1, ERK 2, p38, and JNK, as reported by Suh et al .…”
Section: Mechanism Of Actionmentioning
confidence: 62%
“…The 4T1 cells (2 × 10 5 cells/well) treated with the IC 50 as described in (item 3.5) were washed and resuspended in lysis buffer (2 mM ethylenediaminetetraacetic acid, 10 mM Tris-HCl, 10 mM potassium chloride, 10 mM magnesium chloride) according to [ 41 , 42 , 43 , 44 ] with slight modifications. The pellet was resuspended in lysis buffer, 10% SDS, RNase (10 mg/mL), and Proteinase K (20 mg/mL) and incubated at 55 °C and 37 °C for 10 min.…”
Section: Methodsmentioning
confidence: 99%